Tourism in North East India: From Management’s perspectives - Bhattachraya, Jaydeep (Journal of Commerce and Trade, 2011)
Tourism as an industry is a modern concept but it is now the second largest industry of the present super industrialized world. Its development is considered to be essential because of its anticipated economic benefits of income and employment; as statistics show that it provides jobs to one in every, sixteen workers throughout the world. Tourism is defined as the sum of the relations and services connected with a temporary and voluntary change of residence for non-commercial or non-professional reasons. It is ful1her defined as the sum total of the operations, mainly of an economic nature, which is directly related to the entry, stay and movement of foreigners inside and outside a certain country, city or region. Tourism is an industry composed of a group of firms that are engaged in the business of selling to or serving tourists Hotels, restaurants, transportation and amusements are examples of the types of firm that collectively constitute the Tourism industry. The north east tourism is very rich in all aspect but is unexplored. To make it a vibrant one, the attitudinal change is required. The seven sisters and one brother state can jointly play an active role in promoting tourism in this area. The states are homogenous in character and thus, it will be easy for them to cooperate and reduce cost. For this, an effective organization structure and proper management is required. The paper deals with the same.